PERSAINGAN SOPIR TAKSI DI KOTA PEKANBARU - Muhammad Nazaruddin; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In urban social groups that arise on the basis of professional and employment backgrounds are becoming increasingly diverse. Profession is a job done by someone to earn income, one of which is the profession of taxi drivers. In the city of Pekanbaru there are four taxi companies namely Blue Bird, Riau Taxi, Puskopau, and Kopsi. With many of the number of taxi companies that exist, then every company and taxi drivers must compete in each other to get the welfare of the profession is done, so that researchers want to see in terms of competition is the form of cooperation or conflict that occurred in the middle of competition. The location of the study is the place where the research will be carried out. The location of this research is in Pekanbaru City. The population in this study are all taxi drivers in Pekanbaru City, amounting to 750 people who are divided in four taxi companies. Thanks to the same character, the location is also the same then the author takes 10% of each company using proportional random sampling technique. That is the sampling technique based on the consideration of the number of each subject group. In this competition, every company and taxi driver create strategies to achieve their goals, Through a comparison of four taxi companies known there are differences in strategy that is run, In relation to the strategy, each strategy undertaken determines the dominance between one company with another company. In addition, basically the strategy that runs arise because of the increasingly complex competition, the forms of competition that is clearly visible in this study is the economic competition and competition of existence. And in the competition is also the cooperation that is spontaneous cooperation and contract cooperation that occurred between taxi drivers in Pekanbaru City.Keyword : Competition, Taxi Driver.